Singapore's labour force, labour policy and productivity - Tham, Tuck Meng (2014)
With increasing global and domestic competition, labour policies haw become one of the most important aspects in governmental economic planning. Though Singapore's workforce is well trained among newly industrialised and developing countries, if must be persistent in upgrading its skills and productivity to meet the challenges ahead